Podcast: Basics of Hindfoot Radiography - Claire Sandstrom (Association of American Medical Colleges, 2014)
Abstract This enhanced podcast explores the basics of hindfoot radiography, including definition of the hindfoot, normal anatomy, and radiographic projections obtained for evaluation of hindfoot trauma. This resource is targeted toward newcomers to radiology, including junior radiology residents, medical students, and non-radiology physicians. Also included are suggestions for integration by the educator into teaching and a set of eight multiple-choice questions that can be administered before and after viewing the podcast to assess comprehension. The enhanced podcast format integrates visual and auditory learning into a portable and easily navigable product. Outside the classroom, learners can view the podcast as many times as necessary to feel comfortable with its content, including rewinding or advancing to specific sections. The podcast is designed to be small enough that it could be distributed as an attachment by our university email. In order to attain the smaller file size, some degree of image quality might be sacrificed, but when polled residents favored a smaller file over a larger one containing higher-quality images. The residents were sent the podcast 5 days prior to attending a conference on ankle and hindfoot trauma, with instructions to download and view at least once, though they were encouraged to view as many times as desired to feel comfortable with the material. After attending the conference they were asked to complete an anonymous survey. Respondents reported that the level of the material to be "just right for where I am right now." All of the respondents reported that the podcast improved their understanding of, and ability to engage in, the subsequent conference material.